Islamic finance : the new regulatory challenge - Abdel Karim, Rifaat Ahmed; Archer, Simon , 1957-1993 (Wiley finance, 2013)
With interest in Islamic finance swiftly spreading beyond the Muslim world, the need among finance and investment professionals has never been greater for timely information about the rules governing Islamic finance. This thoroughly updated and revised second edition of the premier guide to regulatory issues in Islamic finance satisfies that need